KONTRIBUSI IKLIM KERJA TERHADAP KREATIVITAS GURU SEKOLAH DASAR NEGERI KECAMATAN TANJUNG HARAPAN KOTA SOLOK - Astrid Permata Putri (Jurnal Bahana Manajemen Pendidikan, 2015)
The result of Informal talk with principal and some teacher in elementary school in tanjung harapan solok city on 18-24 april 2015, show indication that theacher’s creativity to do task and learning process not maximal yet. It is caused not condusif yet This study aims to view its work climate contribute significantly to the creativity of teachers. Population of teachers of 240 people and 82 samples were taken with the Proportional stratified random sampling technique. tested questionnaire to 15 respondents. The research instrument was a Likert scale questionnaire form which has been in testing the validity and reliable. Data analysis show 1) creativity of teacher the elementary school in Tanjung Harapan Solok city in the category higth (81,03%) of the ideal score, 2) work iclimate in the elementary school in Tanjung Harpan Solok city in the category good (83,66%) of the ideal score, 3) great contribution of variable work climate of the creativity teacher's task is r2 0,162 = 1,62%, This means that the working climate affects teachers creativity 16,2 %.Kata kunci: iklim kerja dan kreativitas guru